Principles of CMOS VLSI design : - Weste, Neil H. E. (Addison-Wesley, 1985)
The book deals the technology down to the layout level of detail, thereby providing a bridge from a circuit to a form that may be fabricated. The early chapters provide a circuit view of the CMOS IC design, the middle chapters cover a sub-system view of CMOS VLSI, and the final section illustrates these techniques through the use of a case study. This capstone section ties together the preceding chapters and gives the student a feel for real-world design.